AKTIVITAS EKSTRAK METANOL BONGGOL BUNGA TERATAI (Nymphaea lotus L.) UNTUK PENGENDALIAN CENDAWAN PELAPUK KAYU Schizopyllumcommune Fries SECARA in vitro - Sari, Eka Puspita; Wardenaar, Evy; Yusro, Fathul (JURNAL HUTAN LESTARI, 2013)
The aim of this research was to evaluate the activity methanol extract of lotus plant part (Nymphaea lotus L.) flower excrescenes that best of treatment to inhibit Schizopyllum commune Fries fungus-growth. Research was conducted in several steps, maceration process and efficacy test of methanol exctract as antifungal, agar media used for the treatment was PDA (potatoes dextrose agar). Concentration of methanol exctract used for the treatment were 0;2;4;6;8; and 10%. The result indicated that the methanol exctract inhibited the Schizopyllum commune Fries growth. Concentration of methanol exctract resulted in significantly different antifungal activities. Methanol extract with a concentration of 2% from flower excrescence resulted in 97,62%, the content of organic fractions of methanol exctract, such as alkaloid, tannin, flavonoid might be possible for these antifungal activities. Key words :Lotus, methanol extract, antifungal activities, maceration, Schizopyllum commune Fries